The effect of thickness and laying pattern of paver on concrete block pavement - Md. Nor, Hasanan; Ismail, Che Ros (Universiti Teknologi Malaysia, 2006)
In concrete block pavements, the blocks make up the wearing surface and are a major load-spreading component of the pavement. Earlier findings were inconsistent with respect to the deflection response of concrete blocks in the pavement. This research investigate the anchor beam spacing of concrete block pavement (CBP) on sloping road section based on the degree of slope, laying pattern, blocks shape, blocks thickness, joint width between blocks and bedding sand thickness. The effect of load transfer on the CBP behaviour is discussed. The results of a series of tests conducted in laboratory with horizontal force test and push-in test in several degrees of slopes. The horizontal force testing installation was constructed within the steel frame 2.00 x 2.00 metre and forced from the side until CBP failure (maximum horizontal creep). For the applied push-in test in a rigid steel box of 1.00 x 1.00 metre square in plan and 0.20 meter depth, the vertical load was increased from zero to 51 kN on the CBP sample in 0%, 4%, 8% and 12% degrees of slopes. The herringbone 45o is the best laying pattern compared to herringbone 90o and stretcher bond to restraint the horizontal force, which the blocks contribute as a whole to the friction of the pavement, the blocks being successively locked by their rotation following their horizontal creep. This reduces the incidence of creep and distributes wheel loads more evenly to the underlying pavement construction. The uni-pave block shape has more restraint of horizontal creep than rectangular block shape, because uni-pave block shape has gear (four-dents), while rectangular block shape has no gear (dents).The difference in deflections observed between uni-pave shape and rectangular shape are small. The change in block thickness from 60 to 100 mm significantly reduces the elastic deflection of pavement. Thicker blocks provide a higher frictional area. The load transfer will be high for thicker blocks. The response of the pavement is highly influenced by block thickness. The optimum joint width between blocks is 3 mm. For joint widths less than the optimum, the jointing sand was unable to enter between blocks. A large amount of sand remained outside the joint sand heaps on the block surface. The relationship between push-in force with block displacement on the varying loose thicknesses of 30, 50, and 70 mm bedding sand, shows that the deflections of pavement increase with increase in loose thickness of bedding sand. The deflection is minimum at a loose thickness of 30 mm bedding course. The higher the loose bedding sand thickness, the more the deflection will be. The effect of the degree of slope on concrete block pavements on sloping road section area is significant with friction between blocks and thrusting action between adjacent blocks at hinging points is more effective with thicker blocks. Thus, deflections are much less for thicker blocks with increasing degree of the slope. The spacing of anchor beam is increases with decreasing joint width, degree of slope and bedding sand thickness. To compare results between laboratory test with the simulated mechanical behaviour of concrete block pavements, a structural model based on a Three Dimensional Finite Element Model (3DFEM) for CBP was employed.